(untitled) - Holum, John R. (New York, 1979)
This updated editon explains recent advances in environmental studies and in the molecular basis of life. Suitable for students interested in the health care field as well as those who want to know how nature and human life work at the molecular level, the book begins by providing readers with a solid background in formulas, structures, equations, solutions and equilibria. A number of topics are introduced early, such as molarity, and are discussed in more detail in later chapters. Each chapter contains a summary as well as review exercises.
Keywords: Biochemistry